Meta‐analysis of adjuvant therapy following curative surgery for periampullary adenocarcinoma. Issue 7 (18th May 2017) - Acharya, A.; Markar, S. R.; Sodergren, M. H.; Malietzis, G.; Darzi, A.; Athanasiou, T.; Khan, A. Z.
Abstract: Background: Periampullary cancers are uncommon malignancies, often amenable to surgery. Several studies have suggested a role for adjuvant chemotherapy and chemoradiotherapy in improving survival of patients with periampullary cancers, with variable results. The aim of this meta‐analysis was to determine the survival benefit of adjuvant therapy for periampullary cancers. Methods: A systematic review was undertaken of literature published between 1 January 2000 and 31 December 2015 to elicit and analyse the pooled overall survival associated with the use of either adjuvant chemotherapy or chemoradiotherapy versus observation in the treatment of surgically resected periampullary cancer. Included articles were also screened for information regarding stage, prognostic factors and toxicity‐related events. Results: A total of 704 titles were screened, of which 93 full‐text articles were retrieved. Fourteen full‐text articles were included in the study, six of which were RCTs. A total of 1671 patients (904 in the control group and 767 who received adjuvant therapy) were included. The median 5‐year overall survival rate was 37·5 per cent in the control group, compared with 40·0 per cent in the adjuvant group (hazard ratio 1·08, 95 per cent c.i. 0·91 to 1·28; P = 0·067). In 32·2 per cent of patients who had adjuvant therapy, one or more WHO grade 3 or 4 toxicity‐related events were noted. Advanced T category was associated worse survival (regression coefficient −0·14, P = 0·040), whereas nodal status and grade of differentiation were not. Conclusion: This systematic review found no associated survival benefit for adjuvant chemotherapy or chemoradiotherapy in the treatment of periampullary cancer. Abstract : No benefit